How Condom Discontinuation Occurs: Interviews With Emerging Adult Women. Issue 4 (13th June 2017) - Mullinax, Margo; Sanders, Stephanie; Dennis, Barbara; Higgins, Jenny; Fortenberry, J. Dennis; Reece, Michael
Abstract : We have almost no data on how and when couples stop using condoms. This qualitative study investigated the process of condom discontinuation. From November 2013 to April 2014, a total of 25 women living in a college town in the Midwest, ages 18 to 25, participated in semistructured interviews centered around three domains: partner interactions, contraceptive use, and sexually transmitted infection (STI) prevention. Analysis followed a critical qualitative research orientation. Participants described actively seeking the best options to prevent pregnancy, perceiving condom discontinuation in favor of hormonal methods as a smart decision, and reported wanting to discontinue using condoms due to physical discomfort. Oftentimes, nonverbal communication around contextual instances of condom unavailability paved the way for discontinuation. Participants indicated the decision to stop using condoms was neither deliberate nor planned. Condom discontinuation rarely occurred at one point in time; instead, it was preceded by a period of occasional use. Even after participants described themselves as not using condoms, sporadic condom use was normal (typically related to fertility cycles). This study provides a more detailed understanding of how and why emerging adults negotiate condom discontinuation, thereby enhancing our ability to design effective condom continuation messages. Attention should be paid to helping emerging adults think more concretely about condom discontinuation.